STRATEGI PENANGANAN ILLEGAL, UNREGULATED AND UNREPORTED FISHING (IUU-FISHING) DI PERAIRAN PROVINSI RIAU TAHUN 2014-2016 - Jhon Mayer H. Siahaan; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to explain the strategy of the Indonesian government in dealing with acts of Illegal, Unregulated and Unreported Fishing (IUU Fishing) by a foreign vessel which occurred in Indonesian waters and the waters of Riau Province in particular. Head of Fisheries and Marine Resources in Riau Province, the number of fishermen from the Province of Riau annually exceeds 94,000 tons per year, but the potential catch is supposed to reach 350,000 tons per year. In this study the authors use Neorealism perspective. In his view the theory of International Relations is best to focus on the structure of the system, the units that interact, continuity and change the system. To bridge the problems to the hypothesis the author uses the analysis of the level of the nation-state (nation-states). To be entered into the case of Illegal, Unregulated, and Unreported Fishing (IUU Fishing) is the author uses the theory of John Lovell strategy. The strategy is a measure used to win a battle. Indonesia conduct national and regional strategies such as the establishment of a task force eradication of illegal fishing drownings even foreign ships that make IUU-Fishing. Indonesia also conducts regional and international cooperation to combat illegal, unregulated and unreported fishing together. This study proves the Indonesian government has a strong commitment to combat IUU-fishing in order to realize Indonesia as Country of maritime axis in the world. Keywords: Strategy, Illegal, Unregulated and Unreported Fishing (IUU Fishing), Waters of Riau province, drowning, Foreign Fishing Vessels